Effect of corn husk fibre loading on thermal and biodegradable properties of kenaf/cornhusk fibre reinforced corn starch-based hybrid composites - Hazrol, M.D.; Sapuan, S.M.; Ilyas, R.A.; Zainudin, E.S.; Zuhri, M.Y.M.; Abdul, N.I. (Elsevier, 2023)
This paper documents the thermal and biodegradation behaviour of kenaf/cornhusk fiber reinforced corn starch-based hybrid composites film (CS/K–CH) produced by solution casting method. To develop both components as biodegradable hybrid composite, this research used corn starch as matrix, kenaf fiber and cornhusk fibre as a filler. Changes in physical structure and weight from the soil burial test were measured using Mettler Toledo digital balance ME. Films produced from physically blended corn starch reinforced kenaf biocomposites films (CS/K) biocomposite film had faster biodegradation and lost 96.18% of weight within 10 days compared with corn starch hybrid composites that only lost 83.82% of total weight. It was observed that the control film, CS/K biocomposite film was completely degraded after 10 days, meanwhile it took 12 days for hybrid composite films to be fully degrade. The thermal properties such as TGA and DTG were also measured. Addition of corn husk fiber significantly improve the film's thermal properties. Glass transition temperatures of corn starch hybrid films were significantly lowered when cornhusk compositions were increased from 0.2% wt to 0.8% wt. Importantly, the current work has demonstrated that hybrid films made of corn starch can be a suitable biodegradable material for substitute synthetic plastic.